Arabidopsis Mitochondrial Voltage-Dependent Anion Channels Are Involved in Maintaining Reactive Oxygen Species Homeostasis, Oxidative and Salt Stress Tolerance in Yeast - Sanyal, Sibaji K.; Kanwar, Poonam; Fernandes, Joel Lars; Mahiwal, Swati; Yadav, Akhilesh K.; Samtani, Harsha; Srivastava, Ashish K.; Suprasanna, Penna; Pandey, Girdhar K. (Frontiers in Plant Science, 2020)
Voltage-dependent anion channels (VDACs) are conserved proteins of the mitochondria. We have functionally compared Arabidopsis VDACs using Saccharomyces cerevisiae Δpor1 and M3 yeast system. VDAC (1, 2 and 4) were able to restore Δpor1 growth in elevated temperature, in oxidative and salt stresses, whereas VDAC3 only partially rescued Δpor1 in these conditions. The ectopic expression of VDAC (1, 2, 3 and 4) in mutant yeast recapitulated the mitochondrial membrane potential thus, enabled it to maintain reactive oxygen species homeostasis. Overexpression of these VDACs (AtVDACs) in M3 strain did not display any synergistic or antagonistic activity with the native yeast VDAC1 (ScVDAC1). Collectively, our data suggest that Arabidopsis VDACs are involved in regulating respiration, ROS homeostasis and stress tolerance in yeast.